O capitalismo cor de rosa: o trabalho informal das revendedoras de produtos Mary Kay - Oliva, Giulia (Universidade Federal de São Carlos, 2024)
The present study revolves around the issue of informality in employment, particularly focusing on informal work carried out by women. Through participant observation within a Sales Unit of the Mary Kay company, an ethnography of the meetings and interactions among the sales representatives was conducted to comprehend how the implications of informal work predominantly impact women. By revisiting the literature on informal employment and informal female labor, coupled with an analysis of ethnographic accounts from the Sales Unit, a greater presence of women in the informal market was observed due to the necessity of engaging in flexible positions to ensure financial support and family maintenance. Thus, the study delves into themes such as survival in the job market, the gendered division of labor, and the consequences of informality to shed light on a recurring topic in Labor Sociology, through the gender lens.
Pink capitalism: the informal work of Mary Kay product resellers
Keywords: Trabalho Informal; Gênero e trabalho; Viração; Mary Kay; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS